Performance assessment of the vortex panel method - Sultan, Khalid; Elshabli, Anas; Kashbour, Mohammed; Ben.Ateiga, Seraj (Libyan Journal of Science &Technology, 2022)
The vortex panel method is a very simple and computationally effective method to solve the incompressible and inviscid flow past thin airfoils. This work tries to provide a complete and detailed presentation of the mathematical derivation of this method. It also highlights the points of strength and weakness of this method as compared with more advanced yet expensive computational methods. The results obtained from this work have shown that the method is capable of solving the flow past thin airfoils with good precision for subsonic and laminar flow. For transonic and turbulent flows and as the angle of attack of the flow is increased, the method lacks the precision, especially near the leading and trailing edges.